Robotic Resection of a Posterior Mediastinal Unicentric Castleman#x2019;s Tumor (Global Journal of Medical Research, 2019)
Castleman#x2019;s disease is a rare lymphoproliferative disease, that can either be unicentric or multicentric in presentation. It can affect various sites such as chest, neck, abdomen, and many others. Unicentric Castleman#x2019;s disease commonly affects the mediastinum, arising in the anterior and middle compartment and less commonly the posterior compartment. Patients affected with the disease are usually asymptomatic, however, they may present with non-specific symptoms such as cough and dyspnea. The treatment of Unicetric Castleman#x2019;s disease is surgical resection. In this case report we present a case of posterior mediastinal unicentric Castleman#x2019;s tumor, which was completely resected via robotic surgery.
Keywords: castleman#x2019; s disease; posterior mediastinal mass; robotic resection